TOWARDS SOCIALLY SUSTAINABLE TOURISM IN CITIES: LOCAL COMMUNITY PERCEPTIONS AND DEVELOPMENT GUIDELINES - Silva, Filipa Pinto da (2019)
In the last years, tourism has been growing significantly in urban settings. This growth led to a number of positive impacts, but the uncontrolled expansion of tourism related activities (the ‘overtourism’ effect) has caused many negative outcomes. This paper entails a reflection on sustainable tourism in urban contexts, focusing on locals’ perceptions of tourism impacts on their daily lives. A survey was conducted of 151 residents and workers of the city centre of Porto, Portugal, aiming at a deeper understanding of the social, cultural, and economic, impacts resulting from the exponential development of tourism in the city. The findings suggest that, at this early stage of development, locals agree with the development of tourism in the city and consider that it improved their overall living conditions. However, there are concerns with housing prices and rising cost of living. The resulting data allowed to design a set of guidelines to build a sustainable development model for urban tourism destinations, assuring the local communities’ quality of life, where several preventive measures are presented that aim to preserve the sociocultural sustainability of urban communities.